2020
DOI: 10.1038/s41598-020-61283-w
|View full text |Cite
|
Sign up to set email alerts
|

LC-HRMS based approach to identify novel sphingolipid biomarkers in breast cancer patients

Abstract: perturbations in lipid metabolic pathways to meet the bioenergetic and biosynthetic requirements is a principal characteristic of cancer cells. Sphingolipids (SpLs) are the largest class of bioactive lipids associated to various aspects of tumorigenesis and have been extensively studied in cancer cell lines and experimental models. the clinical relevance of SpLs in human malignancies however is still poorly understood and needs further investigation. in the present study, we adopted a UHpLc-High resolution (or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…It is interesting to note that the upregulation of CERK expression (tumor/normal > 2) is found only in some TNBC patients, with a significant association with chemoresistance (Table 1 ). Previous studies using cell models and publicly available microarray data show that elevated CERK expression is linked with metastatic breast cancer and increased risk of recurrence in patients with breast cancer [ 12 , 13 , 23 ]. Specifically, CERK overexpression is also associated with decreased recurrence-free survival in patients with ER-negative breast cancer [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the upregulation of CERK expression (tumor/normal > 2) is found only in some TNBC patients, with a significant association with chemoresistance (Table 1 ). Previous studies using cell models and publicly available microarray data show that elevated CERK expression is linked with metastatic breast cancer and increased risk of recurrence in patients with breast cancer [ 12 , 13 , 23 ]. Specifically, CERK overexpression is also associated with decreased recurrence-free survival in patients with ER-negative breast cancer [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“… 25 Dysregulation of lipid homeostasis has become an established hallmark of numerous cancers including CRC. 26 , 27 With the exception of CRC, dysregulation of lipid metabolism has also been confirmed in CAA patients. Fecal metabolomics studies of CAA patients have found significantly altered levels of some bioactive lipids (including polyunsaturated fatty acids, secoiric acid, glycerolipids, glycerophospholipids, sterolipids, and sphingolipids) in CAA patients relative to controls.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Metabolomics is developing into a standard tool for future epidemiology and translational cancer research such as applications in clinical diagnosis of colorectal cancer, breast cancer, and bladder cancer. 6 – 8 In the past decade, the development of liquid chromatography‐mass spectrometry (LC‐MS) has revolutionized metabolomics analysis, which led to new biomarker discoveries and a better mechanistic understanding of cancer diagnosis. 9 Among them, ultra-performance liquid chromatography-quadrupole time-of-flight high-definition mass spectrometry (UPLC-QTOF/HDMS) is one of the most sensitive, selective, and reproducible analytical techniques.…”
Section: Introductionmentioning
confidence: 99%